The Rhetoric of Otherness and Humanitarian Imperialism in McCormick’s Sold and Grennan’s Little Princes - Senehang, Dipankar (Sahayaatra सहयात्रा, 2026)
The paper examines the rhetoric of otherness and humanitarian imperialism in Patricia McCormick’s Sold and Conor Grennan’s Little Princes. It centers on the politics of otherness and the narratives of humanism that reinforce white Americans' perceived colonial duty. As the texts portray heroic American protagonists risking their lives to rescue Nepali children from trafficking, McCormick and Grennan subtly perpetuate the white man’s burden and legitimize imperial intervention. The authors depict America as the savior confronting monstrosity, savagery, barbarity, and inhumanity, exoticizing Nepal in the process. Accordingly, the paper addresses three key questions: Why do the writers depict America as the protector of trafficked children? What do they aim to convey through their portrayals of otherness and humanitarian stories? And how do McCormick and Grennan sustain the imperial legacy? To answer these, the paper employs Renato Rosaldo’s idea of imperialist nostalgia and Edward W. Said’s concept of Orientalism. It argues that McCormick and Grennan mourn the harm done to Nepali society, show empathy for the suffering, assume moral responsibility for the damage, and naturalize imperial intervention. They exploit the Oriental gaze over Nepal, justify American superiority, and establish a fundamental East-West divide, with the West positioned as savior and the East as in need of salvation.